Conceiving the Indian Buddhist patriarchs in China - Young, Stuart H., 1974- (Studies in East Asian Buddhism, 2015)
This study sutiates the medieval Chinese hagiographies of Asvaghoa, Nagarjuna, and Aryadeva in the context of Chinese religion, culture, and society of the time. It examines these sources not as windows into ancient Indian history but as valuable records of medieval Chinese efforts to define models of Buddhist sanctity.